1996
DOI: 10.1046/j.1365-3156.1996.d01-15.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HIV‐1 infection on child health in sub‐Saharan Africa: the burden on the health services

Abstract: Summary HIV‐I infection in sub‐Saharan Africa is resulting in substantial child mortality and an increase in the number of sick children presenting to health services. Many of the sick children come to health centres and hospitals, inflating numbers on paediatric wards. The presentations of childhood HIV‐I infection are many and varied so that HIV‐I infection is the new ‘great imitator’ of other conditions. Some other infections are more severe in HIV‐I infected children (specifically bacterial infections and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…In a Nigerian study (in Benin), orphans and vulnerable adolescents were more frequently rejected and isolated at school than the control group children (GECA 2005). This finding is also supported by those of Loudon et al (2007); UNESCO & ESART (2009); Ntaote (2011); Grassly and Timaeus (2003); Foster and Williamson (2000) and Walraven et al (1997).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In a Nigerian study (in Benin), orphans and vulnerable adolescents were more frequently rejected and isolated at school than the control group children (GECA 2005). This finding is also supported by those of Loudon et al (2007); UNESCO & ESART (2009); Ntaote (2011); Grassly and Timaeus (2003); Foster and Williamson (2000) and Walraven et al (1997).…”
Section: Discussionsupporting
confidence: 74%
“…Findings from the study of Ntaote (2011) also showed that orphaned and vulnerable adolescents are severely affected by the stigma of the disease as they are often teased, bulled and gossiped about by other learners and some of their teachers and also experience discrimination and isolation from the members of their extended families. Other studies also confirm that orphans suffer more vulnerability than non-orphans in terms of education (Foster & Williamson 2000;Grassly & Timaeus 2003;Walraven et al 1997). This has been a serious concern especially in Sub-Saharan Africa, which continues to have the highest percentage of the global HIV and AIDS crisis (as evident in the UNAIDS World Report 2011).…”
Section: Résumémentioning
confidence: 93%
“…Southern Africa is thought to have the highest seroprevalence levels, with over 15% of the adult population in Botswana, Zimbabwe and Zambia being seropositive (Weekly Epidemiological Record, 1997). It is estimated that under-®ve mortality rates in urban centres with severe epidemics (30% seroprevalence in sexually active adults) will rise by as much as three-quarters (Walraven et al, 1996). In East Africa seroprevalence is estimated to be slightly lower, with 10±15% of the adult population seropositive in Uganda and Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…HIV/AIDS in sub-Saharan Africa is resulting in substantial child mortality and an increase in the number of sick children presenting to health services (Walraven et al, 1996). HIV infection causes damage of the cell mediated immunity and subsequent development of various opportunistic infections (Lucas, 2002).…”
Section: Introductionmentioning
confidence: 99%